Якісне дослідження динаміки нечітких дискретних систем - Ivohin, E. V.; Volchkov, S. A. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The analysis of the stability-like properties of fuzzy discrete systems functioning on decisions support systems example is carried out. The determination of stability solutions of fuzzy systems is introduced, the belonging function senses calculation algorithms for guaranteeing of decisions support systems dynamics modeling are offered. On the basis of Lyapunov functions method the assertion about conditions of stability in discrete fuzzy systems are proved.